2003
DOI: 10.2320/matertrans.44.907
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Zr-Al-Cu-Ni-Ag Ingot and the Thermal Stability of Corresponding Glass

Abstract: Zr 65 Al 7:5 Ni 10 Cu 12:5 Ag 5 ingots with different microstructures are obtained by changing the number of the repeated arc melting times. Differential scanning calorimetry (DSC) traces show that when the microstructure of the mother ingot becomes finer, the thermal stability of the glassy alloy improves during the crystallization of the glass. Because of the structure heredity, the finer the mother ingot microstructure is, the smaller the average size of the (Zr,Ag)-rich short-range orders in the glassy all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The relatively small values of the incubation and crystallization times (as shown in Table 2) suggest that crystallization initiates from the growth of quenched-in nuclei [14,15]. The assumption is consistent with the observations that nanocrystals of 3-5 nm in size can be detected in the amorphous matrix of Cu-based BMGs [6,7].…”
Section: Resultssupporting
confidence: 85%
“…The relatively small values of the incubation and crystallization times (as shown in Table 2) suggest that crystallization initiates from the growth of quenched-in nuclei [14,15]. The assumption is consistent with the observations that nanocrystals of 3-5 nm in size can be detected in the amorphous matrix of Cu-based BMGs [6,7].…”
Section: Resultssupporting
confidence: 85%
“…Our previous work indicates that the first exothermic process is due to the precipitation of icosahedral phase (I-phase) based on the XRD pattern (not shown here) [5]. And at higher temperature, the residual amorphous phase and I-phase begin to decompose into more stable phases CuZr 2 and (or) NiZr 2 [5]. The detailed DSC data are shown in Table 1.…”
Section: Resultsmentioning
confidence: 66%
“…Much progress has been achieved in the preparation, thermal stability and mechanical properties of MGs in recent decades [4]. It has been reported that icosahedral phase (I-phase) precipitates as the primary phase during heating of the Zr 65 Al 7.5 Cu 12.5 Ni 10 Ag 5 MG [5]. The structural unit of I-phase is one showing a rotational but not translational order [6], which is metastable and tends to decompose into a more stable state.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed isothermal DSC results are shown in Table 2. From the table, it is clear that the incubation time τ (defined as the time scale between the time t 0 and t 1% , where t 0 is the time to reach the annealing temperature and t 1% the time to reach 1% crystallized volume fraction) is very short for different annealing temperatures, which indicates that crystallization starts from the growth of pre-existing quenched-in nuclei [16]. As the annealing temperature decreases, the exothermic peak width (referred to the time between 1 and 95% of transformation into the crystalline state) increases considerably indicating a more sluggish crystallization process.…”
Section: Resultsmentioning
confidence: 99%